2018
DOI: 10.1038/s41598-018-19570-0
|View full text |Cite
|
Sign up to set email alerts
|

Individuals with depressive tendencies experience difficulty in forgetting negative material: two mechanisms revealed by ERP data in the directed forgetting paradigm

Abstract: Although previous studies have shown that individuals with depressive tendencies have deficits in forgetting negative material, the detailed underlying neural mechanisms have not been elucidated. This study examined the intentional forgetting of negative and neutral material in individuals with depressive tendencies in two phases. In the study phase, the participants performed a directed forgetting task, where a total of 320 words were presented to them, each followed by an instructive cue to forget or remembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 87 publications
4
29
0
1
Order By: Relevance
“…The validity of this interpretation is corroborated by the result of this study that positive feelings were correlated with learning rate α. Further, as per previous findings, when individuals with severe depression are presented with both neutral and negative stimuli, they selectively remember only the negative stimuli and have difficulty suppressing the encoding of such stimuli [46].…”
Section: Discussionsupporting
confidence: 81%
“…The validity of this interpretation is corroborated by the result of this study that positive feelings were correlated with learning rate α. Further, as per previous findings, when individuals with severe depression are presented with both neutral and negative stimuli, they selectively remember only the negative stimuli and have difficulty suppressing the encoding of such stimuli [46].…”
Section: Discussionsupporting
confidence: 81%
“…Exclusion criteria included: (i) any lifetime Axis I disorders other than depression according to Structured Clinical Interview for DSM-IV-TR Axis I Disorders, Research Version, Non-patient Edition (SCID-I/NP; First et al ., 2002); (ii) high level of anxiety, i.e. students with STAI-T scores ranked above 75% of the distribution (Xie et al ., 2018); (iii) seizure disorder; (iv) history of head injury with possible neurological sequelae; (v) self-reported prior use of any psychoactive drugs especially medication for depression; and (vi) current alcohol drug dependence.…”
Section: Methodsmentioning
confidence: 99%
“…A great deal of evidence has accumulated in clinical neurophysiology concerning cognitive functions in depressive patients (Mao et al, 2005; Krompinger and Simons, 2011; Dai and Feng, 2012; Zhao et al, 2015; Kiang et al, 2017; Xie et al, 2018). However, only a few studies have focused on the depressive personality disorder (DPS) in healthy young populations (Shimizu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that individuals with depressive tendencies had difficulties suppressing the memory encoding with negative words, while the suppression of memory encoding of neutral words was relatively intact. Furthermore, compared to individuals without depressive tendencies, depressive individuals had larger word-evoked P2 and late positive potential for negative items, as well as enhanced cue-evoked P1 and N2 for the negative items which were required to be forgotten (Xie et al, 2018).…”
Section: Introductionmentioning
confidence: 99%